Export MSME Case Study: Coffee Wood Dog Chew – Transforming Waste into Global Market Opportunity - Iradah Rahman; Sudarmiatin Sudarmiatin; Puji Handayati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Coffee wood products, natural pet chews, have emerged as one of the unique export commodities developed by Micro, Small and Medium Enterprises (MSMEs) PT Eco Choo in Indonesia. This article presents a case study on export dynamics in the coffee wood MSME sector, secondary data analysis comes from online news, company website, books and articles. The analysis includes the profile of MSMEs, product characteristics, global market penetration strategies, determinants of success and challenges faced. The findings show that the high global demand for eco-friendly pet products is a major driver. Success relies heavily on the ability to consistently maintain quality, product and service safety, manage raw material supply chains, utilize digital marketing, and comply with destination market regulations.. This case study of the coffee wood sector underlines the potential of a creative economy based on local natural resources, while highlighting the importance of quality standards and global market understanding for MSMEs looking to upgrade.